The Two-Tube Method for Treating Thoracogastric Airway Fistula - Zhang, Chenchen; Li, Xiaobing; He, Zhanfeng; Wang, Shuai; Yin, Meipan; Ma, Yaozhen; Wu, Gang (The Thoracic and Cardiovascular Surgeon, 2023)
Background Thoracogastric airway fistula (TGAF) is a fatal complication after esophagectomy. Without active treatment, patients may die of intractable pneumonia, sepsis, massive hemoptysis, or respiratory failure. We determined the clinical value of the two-tube method that involves the precise interventional placement of the nasojejunal tube (NJT) and nasogastric tube (NGT) for TGAF.Methods Clinical data of patients with TGAF who had undergone fluoroscopic interventional placement of NJT and NGT were analyzed retrospectively. The paired t-test was used to compare the index values before and after treatment. Statistical significance was set at p < 0.05.Results In total, 212 patients (177 male and 35 female; mean age, 61.3 ± 7.9 years [47–73]) with TGAF who had undergone the two-tube method were included. Posttreatment chest spiral computed tomography and inflammatory indicators showed significantly improved pulmonary inflammation compared with that before treatment. The patients' general condition remained stable. Of 212 patients, 12 (5.7%) underwent surgical repair, 108 (50.9%) received placement of airway stents, and 92 (43.4%) cases only continued treatment with the two-tube method owing to patients' conditions. In total, 47.8% (44/92) patients died of secondary pulmonary infection, bleeding, and primary tumor progression, whereas 52.2% (48/92) patients survived with both tubes.Conclusion The two-tube method, which involves the precise interventional placement of the NJT and NGT, is simple, safe, and effective for treating TGAF. This method is a bridge for successive treatments or a treatment itself for patients who are unsuitable for surgical repair or stent placement.
Keywords: airway (includes related subject matter); esophageal surgery; infection; surgery; complications